Famiglie in affanno: una ricerca sui processi di impoverimento nel Comune di Senigallia - Bronzini, Micol (Cambio. Rivista sulle Trasformazioni Sociali, 2016)
In recent years in Italy economic hardship has afflicted an increasing range of the population: single-parent families, single-earner couples, elderly persons living alone, families in which a wage-earner has lost his/her job. To better understand the biographies and experiences of these “families in distress”, a partnership has been set up between the Interdepartmental Research Center of the Polytechnic University of Marche, the Municipality of Senigallia, Caritas and an important company, which has financed a three-year research program on these issues. The research project, entitled Corporate Social Responsibility in an Integrated Perspective:families at risk of poverty in Senigallia, focuses on how the phenomenon of poverty is changing in the local context. In particular, it analyses families at risk of hardships, that is those families that cannot be defined as poor in a traditional way but that risk, for a variety of factors, being dragged into poverty. The article presents the main results of this empirical research.